Evaluation of the practices of using paracetamol among parents in treating their children in Penang, Malaysia - Ee Theng Yeoh, Angel Wei Ling Goh, Chee Ping Chong (Journal of Applied Pharmaceutical Science, 2021)
Paracetamol is commonly used to treat fever in young children. This study aims to evaluate the practices of using paracetamol among parents from Penang, Malaysia, in treating their children. Data were collected from a total of 93 parents from Penang, Malaysia, in August 2019. Most parents were between 26 and 40 years old (67.7%) and had at least two children (74.2%). About 54.2% of parents had children aged between 4 and 9 years. The majority of parents (87.1%) had used paracetamol to treat their children with 77.9% of them using it for fever. Approximately half of the parents (53.1%) used paracetamol when their children’s body temperatures were between 37.5°C and 38.0°C. Syrup (66.1%) and chewable tablets (20.2%) were the most popular forms of paracetamol used to treat children. The parents mostly use paracetamol every 6 hours (45.7%) and 4 hours (38.3%). Among the 1–3-year-old children who used paracetamol syrup, 37.5% of them have exceeded recommended total daily dose. Conversely, 64.7% of the children aged 10–12 years who consumed paracetamol syrup were found to have below the recommended total daily dose. In conclusion, the practices of using paracetamol among the parents need to be improved to ensure better treatment outcomes for the children.
Keywords: Paracetamol, parents, children, practices, Penang, Malaysia.